2001
DOI: 10.2337/diacare.24.6.1008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild Exercise Training on Glucose Effectiveness in Healthy Men

Abstract: OBJECTIVE -To detect whether mild exercise training improves glucose effectiveness (S G ), which is the ability of hyperglycemia to promote glucose disposal at basal insulin, in healthy men.RESEARCH DESIGN AND METHODS -Eight healthy men (18 -25 years of age) underwent ergometer training at lactate threshold (LT) intensity for 60 min/day for 5 days/week for 6 weeks. An insulin-modified intravenous glucose tolerance test was performed before as well as at 16 h and 1 week after the last training session. S G and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
3
43
0
3
Order By: Relevance
“…Using a conventional minimal model, we previously reported that young distance runners and strength-trained men have a 76 and 30% higher glucose effectiveness (S g ) than that of control subjects, respectively (3,4). In addition, we recently showed that a 6-week mild exercise training improves both the S g and insulin sensitivity (S i ) in healthy men (5). These studies suggest that exercise is one of the unique approaches that may help to increase S g .…”
mentioning
confidence: 99%
“…Using a conventional minimal model, we previously reported that young distance runners and strength-trained men have a 76 and 30% higher glucose effectiveness (S g ) than that of control subjects, respectively (3,4). In addition, we recently showed that a 6-week mild exercise training improves both the S g and insulin sensitivity (S i ) in healthy men (5). These studies suggest that exercise is one of the unique approaches that may help to increase S g .…”
mentioning
confidence: 99%
“…Exercise training is well known to increase insulin sensitivity under normal conditions (15), and to ameliorate impaired insulin action in insulin-resistant humans (16) and experimental animals (17). A previous study from our laboratory demonstrated that a single bout of exercise enhanced insulin sensitivity 24 h later in insulin-resistant high-fat-fed (HF) rats (18).…”
mentioning
confidence: 99%
“…Similarly, moderate to heavy-intensity aerobic training (ie, 60%-95% of maximal heart rate) that was done 3 times a week for 6 months was shown to improve insulin sensitivity in both younger (n = 14; mean [SD] (34). Also, In 8 healthy young men, 18 to 25 years of age, 6 weeks of moderate-intensity cycling performed for 1 hour 5 days a week was capable of increasing their insulin sensitivity and glucose effectiveness (35). lbaftez et al, conducted a study of twice-weekly progressive resistance training for 16 weeks by 10 older men with newly diagnosed T2DM resulted in a 46.3% increase in insulin sensitivity, along with a 7.1% reduction in fasting glycemia and a significant loss of visceral fat (36).…”
Section: Discussionmentioning
confidence: 99%